Гастрономічний бренд території: сутність та структура - Щука Галина; Shchuka Halyna; Scsuka Halina; Безрученков Юрій; Bezruchenkov Yuriy; Медвідь Лариса; Medvid Larisa (Видавничий дім «Гельветика», 2025)
Резюме. Гастрономічний бренд території є одним із найбільш ефективних інструментів, який сприяє зростанню туристичних потоків, економічному розвитку та підвищенню конкурентоспроможності регіону. В статті визначено сутність та розглянуто структуру гастрономічного бренду території. Виокремлено основні складові гастрономічного бренду території, зокрема ті, які стосуються гастрономії (унікальні місцеві продукти, автентична кухня, культура харчування, кваліфіковані кухарі та кулінари, місцеві виробники продуктів, наукові дослідження та система підготовки кадрів), бренду (візуальна ідентичність та маркетингові стратегії), території (наявність туристичної інфраструктури, продовольчих ринків та магазинів крафтової продукції, залученість місцевого населення). Наголошено на важливості етико-орієнтованості гастрономічного бренду території, що полягає в свідомому виробництві та споживанні.

Abstract. The gastronomic brand of a territory is one of the most effective tools that contribute to the growth of tourist flows, economic development, and increased competitiveness of the region. Ukraine has a rich and diverse gastronomic heritage, which allows us to predict the success of the development of domestic and inbound gastronomic tourism, provided that the territory is properly branded. The purpose of the study is to determine the conceptual foundations of the gastronomic brand of the territory and its main components, based on the systematization and generalization of the results of existing theoretical works and the analysis of successful practices. The research methodology is based on the application of a systemic-structural approach focused on studying the gastronomic brand of a territory as a complex system that has a number of interrelated elements, for the determination of which such methods as analysis and synthesis, deduction and induction, comparison and juxtaposition were used. The use of typology and classification allowed dividing gastronomic brands according to certain criteria and identifying the characteristics of each group. As a result of the study, it was found that the gastronomic brand of a territory, as a phenomenon, combines the characteristics of a brand, a territory brand, a destination brand, and gastronomy. The gastronomic brand of a territory is a set of ideas formed in people's minds about the uniqueness and consumer value of a certain destination due to the offer of local and/or authentic dishes. The article highlights the main components of the gastronomic brand of the territory, in particular those related to gastronomy (unique local products, authentic cuisine, nutrition culture, qualified chefs and cooks, local producers of products, scientific research and personnel training system), brand (visual identity and marketing strategies), territory (availability of tourist infrastructure, food markets and craft shops, involvement of the local population). Emphasis is placed on the importance of the ethical orientation of the gastronomic brand of the territory which consists in conscious production and consumption: compliance with ethical standards, rejection of principles that may harm society or the environment, and interaction with all stakeholders.
Gastronomic brand of a territory: essence and structure
Keywords: бренд; бренд території; туристичний бренд території; гастрономічний бренд території; гастрономія